Building an institutional repository at University of Malaya (Malaysia): UM Research Repository - Mohd Faizal, H.; Ranita, H.S.; Ilina, S.M. (2013)
Abstract: Now, more than ever, the way information is stored, retrieved and displayed is changing. The availability of printed materials can be retrieved in digitized format to support knowledge sharing among researchers and students. Indeed, many universities especially Research Universities in Malaysia are heading towards implementing digital content in their organizations. Digital repositories are also one of the initiatives taken by academic libraries in Research Universities to move towards digital library. Preserving records, mainly the research articles are a vital approach as a visibility of researchers and to be on par with the initiatives from other higher ranking universities in the world. The purpose of this paper is to provide summary of the experiences in setting up an institutional repository at University of Malaya Library (UML), focusing some of the key issues that need to be considered, the teamwork involved, the choices made and the challenges overcome. University Malaya Research Repository is an open access digital archive containing details of published and unpublished research work produced by the University of Malaya staff and researchers. In supporting this project, University of Malaya Library chose E-Prints as a tool to embark this initiative in line with the status of an established Research University in Malaysia. In conclusion, digital repositories such as E-Prints sustain the creation of visibility among researchers and students around the world. Access to the data is unlimited and this enables researchers to communicate and set up the networking among them for profession development.